Influence of rate and time of Azolla caroliniana inoculation on its growth and nitrogen fixation and yield of rice (Oryza sativa) - Singh, D P; Singh, P K (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during wet season 1990 and dry season 1991 to study the effect of rate and time of Azolla carolliniana. Wildenow inoculation on its growth. N2-fixation and yield of rice (Oryza sativa L.). In both seasons the delay in Azolla inoculation decreased the fresh weight (l4.0- 47.5%) and nitrogen yield (15.4 - 48.4%) of Azolla as well as the grain (6.1- 20.3%) and straw (6.4 - 22.7%) yields of rice. An increase in the amount of Azoll inoculum significantly increased these attributes, irrespective of the date of inoculation. Azolla inoculated a week after transplanting gave greater biomass and nitrogen yield than that inoculated 3 and 5 weeks after transplanting. The fresh weight and N yield of Azolla were higher (13.7--103.8%) with inoculums of 2.0 tonnes/ha than with that up to 1.0 tonne/ha in the wet season and 15 tones/ha in the dry season. The use of higher inoculum levels was more advantageous under late-inoculation situation. T he grain and straw yields of rice were the highest when Azolla was inoculated 1 week after transplanting and lowest when it was inoculated 5 weeks after transplanting. The former recorded more panicles/m2 than that inoculated 3 and 5 weeks after transplanting. Inoculation at 5 week after transplanting also reduced the grains/panicle.